Analysis of Boundary Layer Flow and Heat Transfer for two Classes of Viscoelastic Fluid Over a Stretching Sheet with Heat Generation or Absorption - Bhattacharyya, K; Uddin, MS; Layek, GC; Pk, W Ali (Bangladesh Journal of Scientific and Industrial Research, 2012)
In this paper, we obtained solutions of boundary layer flow and heat transfer for two classes of viscoelastic fluid over a stretching sheet with internal heat generation or absorption. In the analysis, we consider second-grade fluid and Walter's liquid B. The governing equations are transformed into self-similar ordinary differential equations by similarity transformations. The flow equation relating to momentum is solved analytically and then the heat equation using the Kummer's function. The analysis reveals that for the increase in magnitude of viscoelastic parameter both the velocity and temperature for a fixed point increase for second-grade fluid and both decrease for Walter's liquid B. Due to increase in Prandtl number and heat sink parameter, the thermal boundary layer thickness reduces, whereas increasing heat source parameter increases that thickness. Key words: Boundary layer flow; Heat transfer; Viscoelastic fluid; Stretching sheet; Heat generation or absorption DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9590 BJSIR 2011; 46(4): 451-456